Acute-phase reaction induces a specific complex between hepatic nuclear proteins and the interleukin 6 response element of the rat alpha 2-macroglobulin gene. - Hattori, M (1990)
Interleukin 6 (IL-6) was established as a transcriptional inducer of the rat alpha 2-macroglobulin gene, a prototype liver acute-phase gene. Maximum induction occurred when the 5' flanking sequences of this gene (position -209 to -43) directed expression from the gene's own TATA box and transcription start site. Removal of the hexanucleotide CTGGGA (position -164 to -159) abolished 60-70% of the hormonal induction in FAO1 rat hepatoma cells. This hexanucleotide was defined as the IL-6 response element (IL-6-RE). The IL-6-RE is well conserved in the cytokine-responsive regions of other acute-phase genes and serves as a binding site for nuclear proteins. A characteristic DNA-protein complex (complex I) was formed with nuclear proteins from normal rat livers. A different, hormone-inducible complex (complex II) was assembled specifically with nuclear proteins from acute-phase rat livers or from IL-6-treated human Hep 3B hepatoma cells. Complex II was competitively inhibited by oligonucleotides representing the conserved IL-6-RE sequence from other acute-phase genes. Thus, the proteins building complex II likely participate in a general signal transduction mechanism mediating the transcriptional activation by IL-6 of several acute-phase genes.